INTEGRASI ANTARA PEMERINTAH DAN ULAMA DALAM PENANGANAN COVID-19 DI ACEH - Muazzinah Muazzinah; Zakki Fuad Khalil; Cut Zamharira (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This paper will discuss the integration between the government and the ulama in handling Covid-19 in Aceh. Integration becomes a complete unity if it is involved by multi stakeholders, especially the ulama. Ulama are the most important unifying factor in overcoming differences in public understanding of the Covid-19 in Aceh. This research method uses a description of qualitative analysis, which in this paper aims to find the relationship between the ulama actor network and the government in forming social constructions as an effort to deal with Covid-19 in a preventive, educational and repressive. The findings show that the ulama are considered important because they have charisma and are able to carry fatwas of truth according to the Quran and have a large mass. Characteristically, the people of Aceh have a close relationship with the ulama so that the religious approach is easier to rationalize than the normative, regulatory, and budget-based government approach. For this reason, the ulama are considered to be more capable of controlling the situation in influencing the community to ward off various phenomena so far, such as the Acehnese people do not believe in Covid-19 and still ignore the recommended health protocol from the government.